Quantifying the Impact of Parent–Child Well Interactions in Unconventional Reservoirs - Gizem Yildirim (Fuels)
The objective of this research is to examine the dynamics of parent/child well interaction in unconventional plays, an issue that has gained prominence as high-quality inventory reduces and the number of infill wells escalates. To achieve this, the research will identify and analyze the factors influencing the interaction between parent/child wells and quantify the impacts of time, distance, and geological formation within the context of the DJ basin. The short-term estimate, considered as the next 12 months of cumulative oil production, is forecasted using decline curve analysis (DCA), and the long-term estimates come from the estimated ultimate recovery (EUR) of oil. The impact of the interaction on the parent well is determined as the difference between the recovery of the pre-frac hit and the post-frac hit. The child wells are compared to unaffected wells from the same unit. The average distance between parent and child wells is kept constant, and the time gap between the pre-existing and infill wells is statistically compared to observe the impact of time. The same procedure is followed for distance, orientation, and formation. The findings indicate that stimulation of child wells can lead to a depletion-induced stress shadow around the parent wells, potentially resulting in asymmetrical fracture growth. Consequently, the proximity of parent wells may contribute to a decrease in the performance of the child wells. On the contrary, parent wells with frac hits experienced varied outcomes, including improved production, reduced production, or no noticeable change at all. When the distance between parent and child well decreases, the negative impact on child wells increases. Increasing the time gap between pre-existing wells and infill wells shows an adverse impact on child wells. The impact on child wells was not observed when the parent well had been producing for less than 5 months. An interesting pattern emerged when analyzing the orientation of wells; child wells drilled at a perpendicular angle to their parent wells did not exhibit changes in performance. Within the geological context, the Niobrara Formation was found to have a more substantial negative impact on well interactions than the Codell Formation. In conclusion, time and distance play a crucial role in parent/child well interaction. Despite the existence of studies on parent/child well interactions within the literature, a comprehensive and detailed analysis specifically targeting the DJ Basin—particularly focusing on the intricacies of well interactions within the Niobrara and Codell Formations—has not yet been undertaken.